Balancing social and institutional support: A cross-cultural study of social entrepreneurial intentions in Vietnam and Poland - Cong Doanh Duong (Social Sciences and Humanities Open, 2025)
This study aims to test the combined effects of perceived social support and perceived institutional support on social entrepreneurial intentions within the cross-cultural contexts of Vietnam and Poland, two nations with distinct socio-economic environments. To achieve this objective, a survey was conducted among university students in both countries, resulting in a sample of 401 respondents from Vietnam and 341 from Poland. Polynomial regression with response surface analysis was employed to test the proposed hypotheses and conceptual model. The results show that both perceived social support and perceived institutional support have a significant impact on social entrepreneurial intention. There are notable differences between the two countries: in Vietnam, perceived social support has a stronger influence on the intention to engage in social entrepreneurship, while in Poland, perceived institutional support plays a more significant role. Furthermore, the study highlights that a balanced combination of perceived social support and perceived institutional support maximizes social entrepreneurial intention in both contexts. This research makes significant contributions to the literature on social entrepreneurship by exploring the complex interactions between social and institutional support across different cultural settings, utilizing advanced analytical techniques. Additionally, practical implications are provided for policymakers, educators, and support organizations to develop more effective, culturally sensitive strategies that foster social entrepreneurship in diverse environments.